Complete Genome Sequence of a Novel Highly Pathogenic Porcine Reproductive and Respiratory Syndrome Virus Variant - Wang, Lianghai (American Society for Microbiology, 2012)
Highly pathogenic porcine reproductive and respiratory syndrome (HP-PRRS) emerged in China in 2006, and HP-PRRS virus (HP-PRRSV) has evolved continuously. Here, the complete genomic sequence of a novel HP-PRRSV field strain, JX, is reported. The present finding will contribute to further studies focusing on the evolutionary mechanism of PRRSV.